Etnobotani Tanaman Kelor (Moringa oleifera Lam.) di Desa Kedungbulus Gembong Pati - Dhea Dani, Brintan Yonaka; Wahidah, Baiq Farhatul; Syaifudin, Andang (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2019)
The potential of Moringa tree related to health properties is still not fully utilized by the people in Pati. Mrs. Muryati, a resident of Kedungbulus Village, Gembong Subdistrict, Pati, was one of the residents who was moved to campaign for the use of Moringa leaves. The purpose of this study was to determine public perceptions about the potential of Moringa plants in the village of Kedungbulus Gembong Pati. This research uses survey methods which include: literature study, field observations, interviews using questionnaires, semistructure interview techniques and using random sampling techniques and purposive sampling. Random sampling sampling from the community taken randomly, while purposive sampling sampling from community leaders such as informants of production houses, village heads, shamans etc. The results obtained from the relationship between community and Moringa plants are explained from interviews with the public perception of Moringa plants.